PEMIKIRAN FILSAFAT MORAL IMMANUEL KANT (Deontologi, Imperatif Kategoris dan Postulat Rasio Praktis) - Dahlan, Mohammad (Jurnal Ilmiah Ilmu Ushuluddin, 2009)
Immanuel Kant is a philosopher who successfully defines ethicsin terms of moral imperatives, not in terms of efforts to attain happiness.He also proposes a rational metaphysics as opposed to the speculativemetaphysics. In the context of rational metaphysics, Kant leads his moralphilosophy to religion, even though the latter is not directly put as thefoundation of the former.